The Impact of Nasturtium officinale-MgO Nanopartical on the Immunity of Hypomagnesemic rats - Obaid, Mustafa Majid; Khaleel, Luma Waleed (Journal of Neonatal Surgery, 2025)
This study explores the green synthesis of magnesium oxide nanoparticles (MgONPs) via Nasturtium officinale (watercress) extract and assesses their physicochemical properties and therapeutic effects against furosemide-induced hypomagnesemia in rats. X-ray diffraction (XRD), energy-dispersive spectroscopy (EDS), scanning electron microscopy (SEM), atomic force microscopy (AFM), UV-Vis spectroscopy, and Fourier-transform infrared spectroscopy (FTIR) were used to confirm the biosynthetic process. In this experiment, 40 adult female rats were divided into five groups: control, furosemide-treated (T1), MgONPs-treated (T2), watercress extract-treated (T3), and magnesium sulfate-treated (T4). The antioxidant enzyme activity (catalase and superoxide dismutase), and serum magnesium levels were examined. MgONPs increased granulocyte proliferation, boosted antioxidant enzyme activity, and successfully restored serum magnesium levels.Validated MgONPs' protective function in maintaining immune function. These findings imply that watercress extract and biosynthesized MgONPs have great promise for treating hypomagnesemia and related immunological dysfunctions.